PENGEMBANGAN EKOWISATA BAHARI MELALUI PENINGKATAN USAHA PROMOSI DI DESA BAHOI KECAMATAN LIKUPANG BARAT KABUPATEN MINAHASA UTARA - Andaki, Jardie A.; Aling, Djuwita R.R. (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2017)
AbstractIbM activities in Bahoi Village have been implemented to promote the potential of marine ecotourism. The sustainability of coastal resources with 4 ecosystems (beaches, mangrove, seagrass, and coral reefs) is the spearhead of marine ecotourism promotion. The openness of the people of Bahoi Village to receive domestic and foreign guests as well as road infrastructure to the village also become a plus attraction in promotional activities.In addition to promotional enhancement, training activities are also carried out by the Team of Dikti Dikti Faculty of Fisheries and Marine Science UNSRAT. Training activities referred to, namely graphic photo training and image processing for the purpose of marine ecotourism promotion. Activities intended for the village community after completion of this activity, can up to date information about marine ecotourism, both information photo natural resources, as well as documentation of social and cultural activities that can attract tourists through promotional efforts. Promotion is also done through mass media (Our Newspapers, Posters, and Neon Box).The result of devotion has been done by IbM Team, it can be concluded: 1) The potential of marine ecotourism in Bahoi Village has not been maximally promoted, although there have been several visits from domestic and foreign tourists, 2) Completeness of tropical coastal ecosystem which is still preserved in Bahoi Village besides potential for maritime tourism, also highly compatible for research or educational purposes, 3) promotional activities through personal contacts, has resulted in visits from US tourists for snorkeling and German tourists for research purposes; and 4) results of the IbM Team's promotion to FPIK UNSRAT , has resulted in student visits doing practical activities, so that people's income can be increased through the provision of accommodation and consumption. Likewise, tourists who come for diving and snorkeling contribute not only accommodation and consumption, as well as diving equipment rental.The result of this activity requires several follow up actions: 1) the need for District level Government support for the regulation and sanction of coastal environment protection of Bahoi Village; and 2) The need for proposed research activities related to the capacity building of village communities in supporting marine ecotourism. Keywords: coastal ecosystem, ecotourism, promotion, income AbstrakKegiatan IbM di Desa Bahoi telah terlaksana untuk mempromosikan potensi ekowisata bahari. Kelestarian sumberdaya wilayah pesisir dengan 4 ekosistem (pantai, mangrove, lamun, dan terumbu karang) merupakan ujung tombak promosi ekowisata bahari. Keterbukaan masyarakat Desa Bahoi menerima tamu domestik dan manca negara serta infrastruktur jalan raya menuju desa turut menjadi daya tarik plus pada kegiatan promosi.Selain peningkatan promosi, kegiatan pelatihan juga dilaksanakan oleh Tim IbM Dikti Fakultas Perikanan danIlmu Kelautan UNSRAT. Kegiatan pelatihan dimaksud, yaitu pelatihan foto grafi dan pengolahan gambar untuk tujuan promosi ekowisata bahari. Kegiatan dimaksudkan agar masyarakat desa setelah selesai kegiatan ini, dapat meng-up to date informasi tentang ekowisata bahari, baik informasi foto sumberdaya alam, maupun dokumentasi aktivitas sosial dan budaya yang dapat menarik wisatawan melalui usaha promosi. Promosi juga dilakukan melalui media massa (Koran SWARA Kita, Poster, dan Neon Box).Hasil pengabdian yang telah dilakukan oleh Tim IbM, dapat disimpulkan : 1) Potensi ekowisata bahari di Desa Bahoi belum maksimal dipromosikan, walaupun sudah ada beberapa kunjungan dari wisatawan domestik dan manca negara, 2) Kelengkapan eksosistem pesisir tropis yang masih terpelihara di Desa Bahoi selain potensial untuk wisata bahari, juga sangat kompetibel untuk kepentingan penelitian atau wisata pendidikan, 3) Kegiatan peningkatan promosi melalui hubungan personal, telah menghasilkan kunjungan dari turis Amerika Serikat untuk tujuan snorkling dan turis Jerman untuk tujuan penelitian, dan 4) Hasil promosi Tim IbM ke FPIK UNSRAT, telah menghasilkan kunjungan mahasiswa melakukan kegiatan praktek, sehingga pendapatan masyarakat dapat meningkat melalui penyediaan akomodasi dan konsumsi. Demikian juga turis yang datang untuk penyelaman dan snorkling memberikan kontribusi bukan saja akomodasi dan konsumsi, juga penyewaan peralatan selam.Hasil kegiatan ini memerlukan beberapa tindak lanjut berupa : 1) perlu adanya dukungan Pemerintah setingkat Kabupaten untuk peraturan dan sanksi perlindungan lingkungan pesisir Desa Bahoi; dan 2) Perlunya usulan kegiatan penelitian terkait pengembangan kapasitas masyarakat desa dalam menunjang ekosiwisata bahari. Kata Kunci: ekosistem pesisir, ekowisata, promosi, pendapatan